Performance of OFDM-IM Under Joint Hardware Impairments and Channel Estimation Errors Over Correlated Fading Channels - Asma Bouhlel; Stavros G. Domouchtsidis; Salama S. Ikki; Anis Sakly (IEEE Access, 2017)
Recent studies have proven the potential of orthogonal frequency division multiplexing with index modulation in improving the bit error rate performance and the spectral efficiency, where its performance is evaluated under the assumption of ideal conditions. In this paper, the implementation of this novel transmission technique under realistic circumstances is thoroughly investigated. For this purpose, a new generalized system model that incorporates both imperfect channel state information and hardware impairments is employed and analytical pairwise error probability over correlated Rayleigh and Ricean fading channel is developed. The derived expression is then adapted to determine a tight upper bound of the average bit error probability. Furthermore, asymptotic expression analysis at high signal-to-noise ratio is included. Finally, simulation results are provided to illustrate the accuracy of the proposed theoretical analysis.